2019
DOI: 10.1200/jco.18.01042
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Nivolumab Plus Ipilimumab in Advanced Non–Small-Cell Lung Cancer (CheckMate 568): Outcomes by Programmed Death Ligand 1 and Tumor Mutational Burden as Biomarkers

Abstract: PURPOSE CheckMate 568 is an open-label phase II trial that evaluated the efficacy and safety of nivolumab plus low-dose ipilimumab as first-line treatment of advanced/metastatic non–small-cell lung cancer (NSCLC). We assessed the association of efficacy with programmed death ligand 1 (PD-L1) expression and tumor mutational burden (TMB). PATIENTS AND METHODS Two hundred eighty-eight patients with previously untreated, recurrent stage IIIB/IV NSCLC received nivolumab 3 mg/kg every 2 weeks plus ipilimumab 1 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
367
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 485 publications
(400 citation statements)
references
References 28 publications
10
367
3
2
Order By: Relevance
“…52 In clinical trials, nivolumab and ipilimumab combination therapy achieved an overall response rate of 43% in unselected patients with NSCLC, compared with 23% in the nivolumab monotherapy group; and in the PD-L1 positive subgroup, nivolumab in combination with ipilimumab showed a response rate of 57%, whilst nivolumab alone was 28% (CheckMate 012 study). 54 However, adverse events of grade 3 or above of combination therapy reached 37%, thereby limiting the widespread clinical application. 54 However, adverse events of grade 3 or above of combination therapy reached 37%, thereby limiting the widespread clinical application.…”
Section: Combination Immunotherapymentioning
confidence: 99%
“…52 In clinical trials, nivolumab and ipilimumab combination therapy achieved an overall response rate of 43% in unselected patients with NSCLC, compared with 23% in the nivolumab monotherapy group; and in the PD-L1 positive subgroup, nivolumab in combination with ipilimumab showed a response rate of 57%, whilst nivolumab alone was 28% (CheckMate 012 study). 54 However, adverse events of grade 3 or above of combination therapy reached 37%, thereby limiting the widespread clinical application. 54 However, adverse events of grade 3 or above of combination therapy reached 37%, thereby limiting the widespread clinical application.…”
Section: Combination Immunotherapymentioning
confidence: 99%
“…Results of the Phase II CheckMate 568 study confirmed that high TMB (determined by the FoundationOne CDx assay), irrespective of PD-L1 status, is associated with improved rates of response to nivolumab plus ipilimumab in patients with advanced NSCLC [79]. ORRs were 9, 15 and 44% for patients with <5, 5 to <10 and ≥10 mutations/Mb, respectively; however, no additional benefit was noted for patients with higher TMB, suggesting that a TMB of ≥10 mutations/Mb is a clinically useful cut-off for the selection of patients most likely to respond to first-line nivolumab plus ipilimumab.…”
Section: Clinical Efficacy Of First-line Nivolumab Plus Ipilimumabmentioning
confidence: 80%
“…The study did not find a meaningful correlation between TMB and PD-L1 expression [79]. Although both PD-L1 expression ≥1% and TMB ≥10 mutations/Mb were associated with higher ORR, PD-L1 expression appeared to have little influence on ORR in patients with high TMB (Table 1).…”
Section: Clinical Efficacy Of First-line Nivolumab Plus Ipilimumabmentioning
confidence: 83%
See 2 more Smart Citations